The Effect of Independence, Due Professional Care, and Experience on Audit Quality - Bayu Bayu; Harry Budiantoro; Kanaya Lapae; Supriyatin Supriyatin; Hesty Juni T S (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
In order to determine how independence, appropriate professional care, and experience affect audit quality at the Public Accounting Firm (KAP) in North Jakarta, this study will look at these factors. The respondents in this study were auditors from the North Jakarta Public Accounting Firm (KAP). In this study, 50 respondents representing 6 Public Accounting Firms (KAP) in North Jakarta served as the sample of auditors. Convenience sampling, or selecting the sample that can be found the easiest, was used to select the sample for this study. While researchers use multiple regression analysis as a data processing technique. According to the study's findings, independence, due professional care, and experience all significantly and favorably affect audit quality.